Mosaic evolution in an asymmetrically feathered troodontid dinosaur with transitional features - Xing Xu (Nature Portfolio, 2017)
Troodontids were theropod dinosaurs closely related to birds. Here, Xu and colleagues describe a new, feathered troodontid species,Jianianhualong tengi, dating from the Lower Cretaceous period in China that provides insight into troodontid mosaic evolution and paravian feathering.